2018
DOI: 10.1590/1676-0611-bn-2017-0385
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofauna of the inner shelf of Paraná, Brazil: checklist, geographic distribution, economic importance and conservation status

Abstract: Comprehensive species checklists are essential to effectively implementing preservation and recovery measures, and should assess conservation status, vulnerability degree and anthropogenic threats. This checklist was compiled from fish species recorded in surveys conducted over the last 30 years in the shallow inner continental shelf in the State of Paraná, Brazil. Information on biogeography, conservation status, economic importance and degree of species' vulnerability are provided. A total of 272 fish specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
(34 reference statements)
0
12
0
18
Order By: Relevance
“…These authors also suggest that P. brasiliensis is not present in Uruguayan waters and that the distribution range limits from San Luis de Maranhao (Maranhao) to Ilha Grande Bay (Rio de Janeiro), Brazil. However P. brasiliensis has been cited for the State of San Pablo waters [39] and also confirmed its presence for Paranaguá and Parana coastal waters of Brazil [40,41], respectively. In practice, P. orbignyanus and P. patagonicus were the species most difficult to differentiate morphologically onboard, although the most noticeable features to differentiate these species are their scales (cycloid in P. orbignyanus and ctenoid in P. patagonicus) and the beginning of the anal fin [42] as well as other morphological characteristics [4].…”
mentioning
confidence: 72%
“…These authors also suggest that P. brasiliensis is not present in Uruguayan waters and that the distribution range limits from San Luis de Maranhao (Maranhao) to Ilha Grande Bay (Rio de Janeiro), Brazil. However P. brasiliensis has been cited for the State of San Pablo waters [39] and also confirmed its presence for Paranaguá and Parana coastal waters of Brazil [40,41], respectively. In practice, P. orbignyanus and P. patagonicus were the species most difficult to differentiate morphologically onboard, although the most noticeable features to differentiate these species are their scales (cycloid in P. orbignyanus and ctenoid in P. patagonicus) and the beginning of the anal fin [42] as well as other morphological characteristics [4].…”
mentioning
confidence: 72%
“…occurred in all sample sites. There are three species of this genus present in the region: C. arenaceus C. macrops and C. spilopterus (Spier et al 2018). Recent studies have also found Cathorops spixii abundantly (Possatto et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine species were on the red list of the International Union for Conservation of Nature (IUCN, 2020), in which 43 are classified as of least concern, and four species as data deficient. Hippocampus reidi and Pseudobatos percellens were classified as near threatened; both are considered as species of economic importance in aquarium trade and as a fishery resource, respectively (Spier et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The description, morphometric measurements and meristic counts of the observed specimen confirm that it is P. macrolepis (Carpenter & DeAngelis, ; Froese & Pauly, ; Snoeks & Vreven, ). The specimen has XIII+16 dorsal‐fin rays, III + 7 anal‐fin rays and 1 + 5 pelvic‐fin rays (Table ) and can be distinguished from native species of Haemulidae catalogued in the Paraná State (Spier et al ., ) by its dark brown body colour and rounded caudal fin (Figure c).…”
Section: Morphometric and Meristic Counts Of The Plectorhinchus Macromentioning
confidence: 97%
“…The Paraná State, in southern Brazil, has a short coastline of c . 90 km; nonetheless, its mangrove areas and sandy beaches and islands maintain a community of 272 species of fish (234 Actinopterygii and 38 Elasmobranchii; Spier et al ., ). In addition, non‐native species reported in this region can be added in the current list (Adelir‐Alves et al ., ; Bornatowski et al ., ; Caires et al ., ; Sampaio et al ., ; Soeth et al ., ).…”
Section: Morphometric and Meristic Counts Of The Plectorhinchus Macromentioning
confidence: 99%